Nıkaıa'dan yeni yazıtlar IV: İznik arkeoloji müzesi (BURSA) - (:unkn) unknown (My University, 2013)
Özet: 2011 yılında Gül Karaüzümün (Müze Müdür Vekili) izniyle İznik Arkeoloji Müzesinde çalışılmıştır. Makalede, İznik Arkeoloji Müzesinden yayımlanmamış 4 yeni yazıt tanıtılmaktadır: 1) Tiberius Caudiusun oğlunun Ana Tanrıçaya bir adağı; 2) Hostilia Briseisin oğlu Briseianus ve ev halkı için Artemise adağı; 3) Zeus Sotere bir adak; 4) Bouleutes [...] Severus, eşi Casia Maxima ile yeğeni Pontia Pactumeianın mezarı. Roma İmparatorluk Dönemine tarihlenen yazıtlar İznik İlçesinden (Bursa) toplanmıştır.

Abstract: Epigraphic research was conducted in the Iznik Archaeological Museum (Bursa) in 2011 with the permission of Gül Karaüzüm (acting Director of the Museum). This paper introduces a compilation of 4 unpublished inscriptions which are now in the museum: 1) A votive offering of Tiberius Caudius son to the Mother Goddess; 2) A votive offering of Hostilia Briseis to Artemis for her son Briseianus and his household; 3) A dedication to Zeus Soter; 4) The graves of bouleutes ... Severus, his wife Casia Maxima and his nephew Pontia Pactumeia. These inscriptions dating from the Roman Imperial Period were collected from the Iznik region (Bursa).
New ınscrıptıons from nıcaea IV: Iznık a rchaeologıcal museum (BURSA)
Keywords: Arkeoloji